Predicting Which Species Succeed in Climate-Forced Polar Seas - Morley, Simon A.; Barnes, David K. A.; Dunn, Michael J. (Frontiers in Marine Science, 2019)
Understanding the mechanisms which determine the capacity of any species to adapt to changing environmental conditions is one of the foremost requirements in accurately predicting which populations, species and clades are likely to survive ongoing, rapid, climate change. The polar oceans are amongst the most rapidly changing environments on earth with reduced regional sea ice duration and extent, and their faunas expected sensitivity to warming and acidification. These changes potentially pose a significant threat to a number of polar fauna. There is, therefore, a critical need to assess the vulnerability of a wide range of species to determine the tipping points, or weak links in marine assemblages. Knowledge of the effect of multiple stressors on polar marine fauna has advanced over the last 40 years, but there are still many data gaps. This study applies ecological risk assessment techniques to the increasing knowledge of polar species’ physiological capacities to identify their exposure to climate change and their vulnerability to this exposure. This relatively rapid, semi-quantitative assessment, provides a layer of vulnerability on top of climate envelope models, until such times as more extensive physiological data sets can be produced. The risk assessment identified more species that are likely to benefit from the near future predicted change (the winners), especially predators and deposit feeders. Fewer species were scored at risk (the losers), although animals that feed on krill were consistently as under the most risk.